Genome of the Rio Pearlfish (Nematolebias whitei), a bi-annual killifish model for Eco-Evo-Devo in extreme environments. Issue 4 (21st February 2022) - Thompson, Andrew W; Wojtas, Harrison; Davoll, Myles; Braasch, Ingo
Abstract: The Rio Pearlfish, Nematolebias whitei, is a bi-annual killifish species inhabiting seasonal pools in the Rio de Janeiro region of Brazil that dry twice per year. Embryos enter dormant diapause stages in the soil, waiting for the inundation of the habitat which triggers hatching and commencement of a new life cycle. Rio Pearlfish represents a convergent, independent origin of annualism from other emerging killifish model species. While some transcriptomic datasets are available for Rio Pearlfish, thus far, a sequenced genome has been unavailable. Here, we present a high quality, 1.2 Gb chromosome-level genome assembly, genome annotations, and a comparative genomic investigation of the Rio Pearlfish as representative of a vertebrate clade that evolved environmentally cued hatching. We show conservation of 3D genome structure across teleost fish evolution, developmental stages, tissues, and cell types. Our analysis of mobile DNA shows that Rio Pearlfish, like other annual killifishes, possesses an expanded transposable element profile with implications for rapid aging and adaptation to harsh conditions. We use the Rio Pearlfish genome to identify its hatching enzyme gene repertoire and the location of the hatching gland, a key first step in understanding the developmental genetic control of hatching. The Rio Pearlfish genome expands the comparative genomic toolkit available to study convergent origins of seasonal life histories, diapause, and rapid aging phenotypes. We present the first set of genomic resources for this emerging model organism, critical for future functional genetic, and multiomic explorations of "Eco-Evo-Devo" phenotypes of resilience and adaptation to extreme environments.